Preparation method and application of high-strength low-shrinkage polyester yarn

By adopting the preparation method of high-elastic polyester yarn, using modified tree ash and modified polyester segments, the problem of large thermal shrinkage rate of existing high-strength polyester yarn is solved, and the preparation of high-strength and low-shrinkage polyester yarn is achieved, which is suitable for for the application of high-performance fibers.

CN119332371APending Publication Date: 2025-01-21ZHUJI JUNQI CHEM FIBER CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411459976.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-17
Publication Date
2025-01-21

AI Technical Summary

Technical Problem

Existing high-strength polyester wires have a high heat shrinkage rate during heat treatment, limiting their use in tires and other high-performance applications.

Method used

The preparation method of high-elastic polyester yarn includes the use of polyester masterbatch, polylactic acid fiber powder, thermoplastic polyurethane elastomer, compatibilizer, modified tree ash and antioxidant, and is made by esterification and modification of modified polyester. Polycondensation reaction to form polyester segments with low thermal shrinkage.

Benefits of technology

The preparation of high -intensity and low contraction polyester wire was achieved, and the dry heat contraction rate was reduced to 2.2 ± 0.3 %, which was suitable for the application of high -performance fibers.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005091600000000051
    Figure BDA0005091600000000051
Patent Text Reader

Abstract

The invention relates to the related technical field of polyester yarn processing, and discloses a preparation method and application of a high-strength low-shrinkage polyester yarn, and the high-strength low-shrinkage polyester yarn comprises a polyester chain segment and a high-elastic polyester yarn; the high-elastic polyester yarn comprises the following components in parts by mass. By means of calcium maleate grafted EVA in the high-elastic polyester yarn, the compatibility of the thermoplastic polyurethane elastomer and the polyester master batch can be improved; the maleic anhydride grafted HDPE has excellent tensile property and high cohesiveness, and the maleic anhydride grafted HDPE and the maleic anhydride grafted HDPE are cooperatively added into the preparation raw materials of the polyester yarn, so that the raw materials for preparing the polyester yarn can be more uniformly combined, and meanwhile, the elasticity of the prepared polyester yarn can be improved; and the movement ability of a molecular chain segment can be effectively reduced through physical cross-linking points or chemical cross-linking points, the rate of conversion from a system to an equilibrium state is reduced, and macroscopically, the shrinkage rate of the size is reduced. Meanwhile, the stability of the cross-linking points is beneficial to improving the interaction force between molecular chains of the cross-linking points and reducing the shrinkage rate.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field related to polyester yarn processing, and in particular to a preparation method and application of high-strength and low-shrinkage polyester yarn. Background Art

[0002] Polyester yarn is a yarn spun from polyester as raw material. Polyester is one of the important varieties of synthetic fibers. It is a fiber made from polyethylene terephthalate (PET) obtained by esterification or ester exchange condensation reaction of purified terephthalic acid or terephthalate and ethylene glycol as raw materials, and is obtained by spinning and post-processing.

[0003] The disadvantage of high-strength polyester yarn is that it has large thermal shrinkage. When using them to prepare tires, it is necessary to adjust the heat treatment conditions of the cord fabric to reduce the shrinkage and increase the modulus. With the increasing production of polyester fibers, people's requirements for fiber quality are also increasing, and fibers are often required to have excellent mechanical properties. For example, fibers used to prepare automotive seat belts and household or industrial sunshades often need to have low dry heat shrinkage. However, due to the large thermal shrinkage of fibers prepared by the prior art, the application of polyester industrial yarns is restricted. In order to solve this problem, a preparation method and application of high-strength and low-shrinkage polyester yarns are proposed. Summary of the invention

[0004] The present invention provides a preparation method and application of high-strength and low-shrinkage polyester yarn, which solves the problems in the above-mentioned background technology.

[0005] The present invention solves the technical problem by adopting the following technical solutions:

[0006] A method for preparing high-strength and low-shrinkage polyester yarn, comprising polyester segments and high-elastic polyester yarn;

[0007] The high-elastic polyester yarn comprises the following components in parts by weight: 60-80 parts of polyester masterbatch; 25-30 parts of polylactic acid fiber powder; 5-10 parts of thermoplastic polyurethane elastomer; 2-5 parts of compatibilizer; 12-18 parts of tree ash; and 2-3 parts of antioxidant.

[0008] The tree ash is modified tree ash, and the preparation method of the modified tree ash is as follows: firstly boil the tree ash with 15-20% hydrogen peroxide for 18 minutes, then wash it with distilled water, dry it in an oven at 110-120°C, add 5-8 parts by weight of sodium lignin sulfonate, 2-3 parts of polyisobutylene, and 5-7 parts of talc, stir it at high speed in a water bath at 80-90°C for 2-3 hours, dry it, crush it into ultrafine powder, and then obtain the modified tree ash;

[0009] The polyester chain segment comprises a terephthalic acid chain segment, an ethylene glycol chain segment and a 2,5-pyridinedicarboxylic acid chain segment, and the 2,5-pyridinedicarboxylic acid chain segments of different polyester chain segments are coordinated by Cu2+; the molar ratio of the terephthalic acid chain segment to the 2,5-pyridinedicarboxylic acid chain segment is 1:0.03-0.05; the 2,5-pyridinedicarboxylic acid chain segment has an O atom on a carbonyl group and an N atom on a pyridine involved in the coordination; the dry heat shrinkage rate of the low heat shrinkage polyester industrial yarn is 2.2±0.3% under the conditions of 177°C, 10min and 0.05cN / dtex.

[0010] Preferably, the compatibilizer is a mixture of maleic anhydride grafted EVA and maleic anhydride grafted HDPE in a mass ratio of 1-2:0.5-1.2.

[0011] Preferably, the modified polyester is solid-phase polycondensed to increase viscosity and then wound with high-elastic polyester yarn to obtain high-strength, low-shrinkage polyester yarn; the preparation method of the modified polyester is: terephthalic acid, ethylene glycol, 2,5-pyridinedicarboxylic acid and cupric chloride are uniformly mixed and then subjected to esterification reaction and polycondensation reaction in sequence to obtain the modified polyester.

[0012] Preferably, the preparation steps of the modified polyester are as follows:

[0013] Esterification reaction: terephthalic acid, ethylene glycol, 2,5-pyridinedicarboxylic acid and cupric chloride are prepared into slurry, a catalyst and a stabilizer are added and mixed evenly, and then the esterification reaction is carried out under pressure in a nitrogen atmosphere. The pressure is normal pressure to 0.3 MPa, the temperature of the esterification reaction is 250 to 260°C, and the termination condition of the esterification reaction is: the amount of water distilled in the esterification reaction reaches more than 90% of the theoretical value;

[0014] Polycondensation reaction: After the esterification reaction is completed, the polycondensation reaction in the low vacuum stage begins under negative pressure conditions. The pressure in this stage is steadily pumped from normal pressure to an absolute pressure below 500 Pa within 30 to 50 minutes. The reaction temperature is 250 to 260°C and the reaction time is 30 to 50 minutes. Then, the vacuum is continued to be pumped to carry out the polycondensation reaction in the high vacuum stage, so that the reaction pressure is further reduced to an absolute pressure below 100 Pa. The reaction temperature is 270 to 282°C and the reaction time is 50 to 90 minutes to obtain modified polyester.

[0015] Preferably, the molar ratio of terephthalic acid, ethylene glycol and 2,5-pyridinedicarboxylic acid is 1:1.2-2.0:0.03-0.05, the amount of cupric chloride added is 20-30 mol% of 2,5-pyridinedicarboxylic acid, and the amounts of catalyst and stabilizer added are 0.01-0.05 wt% and 0.01-0.05 wt% of the amount of terephthalic acid added, respectively.

[0016] Preferably, the catalyst is antimony trioxide, antimony glycol or antimony acetate, and the stabilizer is triphenyl phosphate, trimethyl phosphate or trimethyl phosphite.

[0017] Preferably, the intrinsic viscosity of the modified polyester after solid phase polycondensation thickening is 1.0 to 1.2 dL / g.

[0018] The invention discloses an application of a method for preparing high-strength and low-shrinkage polyester yarn, which is applied in the field of textiles and clothing.

[0019] The advantages and positive effects of the present invention are: the compatibility of thermoplastic polyurethane elastomer and polyester masterbatch can be improved by setting calcium maleate grafted EVA in high-elastic polyester yarn; maleic anhydride grafted HDPE has excellent tensile properties and high adhesion, and the two are added to the raw materials for preparing polyester yarn, which is conducive to making the raw materials for preparing polyester yarn more evenly combined, and at the same time, it is conducive to improving the elasticity of the prepared polyester yarn, and the movement ability of molecular chain segments can be effectively reduced through physical crosslinking points or chemical crosslinking points, and the rate of system conversion to equilibrium state is reduced, which is manifested in the reduction of size shrinkage rate in macroscopic terms. At the same time, the stability of the crosslinking point is conducive to improving the interaction force between molecular chains at the crosslinking point, which is beneficial to reducing the shrinkage rate. DETAILED DESCRIPTION

[0020] The present invention will now be described in further detail.

[0021] Polyester yarn is a yarn spun from polyester as raw material. Polyester is one of the important varieties of synthetic fibers. It is polyethylene terephthalate (PET) obtained by esterification or transesterification polycondensation reaction of purified terephthalic acid or terephthalate and ethylene glycol as raw materials. The fiber is obtained by spinning and post-treatment. The disadvantage of high-strength polyester yarn is large thermal shrinkage. When using them to prepare tires, it is necessary to adjust the heat treatment conditions of the cord fabric to reduce the shrinkage rate and increase the modulus. With the increasing output of polyester fibers, people's requirements for fiber quality are also increasing. Fibers are often required to have excellent mechanical properties. For example, fibers used to prepare automotive seat belts and household or industrial sunshades often need to have low dry heat shrinkage. However, due to the large thermal shrinkage in the fibers prepared by the prior art, the application of polyester industrial yarns is restricted. In order to solve this problem, a preparation method and application of high-strength and low-shrinkage polyester yarns are proposed, including polyester segments and high-elastic polyester yarns.

[0022] The high-elastic polyester yarn comprises the following components in parts by weight: 60-80 parts of polyester masterbatch; 25-30 parts of polylactic acid fiber powder; 5-10 parts of thermoplastic polyurethane elastomer; 2-5 parts of compatibilizer; 12-18 parts of tree ash; and 2-3 parts of antioxidant.

[0023] The tree ash is modified tree ash, and the preparation method of the modified tree ash is as follows: firstly boil the tree ash with 15-20% hydrogen peroxide for 18 minutes, then wash it with distilled water, dry it in an oven at 110-120°C, add 5-8 parts by weight of sodium lignin sulfonate, 2-3 parts of polyisobutylene, and 5-7 parts of talc, stir it at high speed in a water bath at 80-90°C for 2-3 hours, dry it, crush it into ultrafine powder, and then obtain the modified tree ash;

[0024] The polyester chain segment comprises a terephthalic acid chain segment, an ethylene glycol chain segment and a 2,5-pyridinedicarboxylic acid chain segment, and the 2,5-pyridinedicarboxylic acid chain segments of different polyester chain segments are coordinated by Cu2+; the molar ratio of the terephthalic acid chain segment to the 2,5-pyridinedicarboxylic acid chain segment is 1:0.03-0.05; the 2,5-pyridinedicarboxylic acid chain segment has an O atom on a carbonyl group and an N atom on a pyridine involved in the coordination; the dry heat shrinkage rate of the low heat shrinkage polyester industrial yarn under the conditions of 177°C, 10min and 0.05cN / dtex is 2.2±0.3% ; The setting of calcium maleate grafted EVA in high elastic polyester yarn can improve the compatibility of thermoplastic polyurethane elastomer and polyester masterbatch; maleic anhydride grafted HDPE has excellent tensile properties and high adhesion. The combination of the two added to the raw materials for preparing polyester yarn is conducive to making the raw materials for preparing polyester yarn more evenly combined, and at the same time, it is conducive to improving the elasticity of the prepared polyester yarn, and the physical crosslinking points or chemical crosslinking points can effectively reduce the mobility of molecular chain segments, and the rate of transformation of the system to the equilibrium state is reduced, which is manifested in the macroscopic reduction of the size shrinkage rate. At the same time, the stability of the crosslinking point is conducive to improving the interaction force between the molecular chains of the crosslinking point, which is beneficial to reducing the shrinkage rate.

[0025] It should be noted that the spinning process parameters in the above-mentioned entire preparation process are shown in the following table:

[0026]

[0027] In addition, for polyester industrial yarn, although it is subjected to high stress stretching and high temperature heat setting during the forming process, forming highly crystalline and highly oriented structural characteristics, due to the limited mobility of high molecular weight polyester molecular segments (i.e., long relaxation time), and the limited crystallization time during the hot stretching and heat setting process on the spinning process, some of the segments that are not arranged into the lattice are in a straightened or entangled state with higher energy, and are stably "frozen" in this state at room temperature due to the decrease in temperature, far from reaching the thermodynamic equilibrium state. Therefore, during the heating process of polyester industrial yarn, that is, under the condition of 177°C, this part of the "frozen" segment is first "thawed", and the mobility increases, that is, the deorientation of the amorphous region occurs. This effect is particularly obvious under high temperature and short heating time. The occurrence of deorientation will cause the fiber to shrink. At the same time, the shrinkage of polyester industrial yarn is closely related to the crystallinity and the integrity of the crystallization.

[0028] Furthermore, when the copper chloride molecules mentioned above are dispersed into the fibers of the polyester industrial yarn, the copper chloride molecules combine with the ligands in the macromolecules to form relatively stable coordination structure units. The formation of metal-ligand coordination interactions enhances the intermolecular interactions and forms physical crosslinking points, so that the "frozen" segments in the amorphous region are truly "frozen", effectively reducing the thermal motion of the segments in the amorphous region. More energy is required to "thaw" the "frozen" segments, increasing the difficulty of deorientation of the amorphous region, thereby reducing the thermal shrinkage of the polyester industrial yarn. At the same time, the ligand used in the present invention is 2,5-pyridinedicarboxylic acid. When 2,5-pyridinedicarboxylic acid is introduced to replace terephthalic acid, since the positions of the two carboxyl groups are in the para position of the pyridine ring, which is highly similar to terephthalic acid, the influence on the regularity of the formed polyester structure is reduced, thereby not affecting the crystallinity and the integrity of the crystallization.

[0029] It should also be noted that, from a thermodynamic point of view, orientation reduces the entropy of the polymer system, thereby increasing the free energy. Compared with the state before stretching, it is an unstable thermodynamic state and will spontaneously transform into a non-oriented state - de-orientation. The speed of this process depends on kinetic factors. The motion units of polymer molecules are multi-faceted and have different relaxation processes, which depend on temperature. Rapid cooling and quenching after stretching can "freeze" the oriented structure. If such a system is kept at a low temperature, the rate of transformation to the equilibrium state is very slow, but at a higher temperature, the molecular motion intensifies, and the rate of transformation of the system to the equilibrium state increases, which is manifested as a shrinkage of size on a macroscopic scale. At the same time, the movement of various motion units of the polymer is closely related to its stress state. There are interaction forces between and within molecular chains; macromolecular chains also have topological entanglements and physical entanglements, such as condensed entanglements and microcrystals. Continuous polymer chains and entanglements that play a physical cross-linking role form a physical network structure. For oriented polymer materials such as crystallizable fibers, when analyzing their thermal shrinkage behavior, it is necessary to consider the possible influence of the existence of crystalline regions on the movement of amorphous region segments.

[0030] Additionally, the preparation method of the above-mentioned high-elastic polyester yarn is as follows:

[0031] S1: Material pretreatment: Dry the polyester masterbatch of corresponding weight parts at 85℃~90℃ for 3~4 hours to remove the surface moisture of the polyester masterbatch; Dry the polylactic acid fiber powder and thermoplastic polyurethane elastomer of corresponding weight parts in a drying oven at 70℃~80℃ for 1~2 hours;

[0032] S2: Add the polyester masterbatch, polylactic acid fiber powder, thermoplastic polyurethane elastomer, compatibilizer, and antioxidant obtained in step S1 into a high-speed stirrer, and mix and stir at room temperature for 3 to 4 hours to obtain a mixture A;

[0033] S3: adding the mixture A into the screw extruder through the main feeding port, controlling the processing temperature of the screw extruder at 220-280°C, extruding after melting to obtain a melt B; cooling the melt B to form a polyester filament C, and sequentially feeding the polyester filament C through the first roller, heating the upper hot box, stretching the second roller, shaping the lower hot box, and further shaping the third roller to obtain a polyester filament D;

[0034] S4: coating with oil, the polyester yarn D obtained in S3 moves from the third roller to the coating area, an oiling roller coated with oil is provided in the coating area, the oiling roller coats the surface of the polyester yarn D with oil, after the oiling roller coats the surface of the polyester yarn D with oil, stretching is performed, a fourth stretching roller group is provided between the oiling roller and the winding roller, the fourth stretching roller group stretches the polyester yarn D, the stretching multiple is 1.1 to 1.3, the stretching temperature of the fourth stretching roller group is 110 to 130°C, and then the winding roller winds up the polyester yarn D;

[0035] S5: twisting the polyester yarn C into yarn, then drying it, and then keeping it at 80-90° C. for 10-15 minutes to obtain a high-elastic polyester yarn.

[0036] Furthermore, the oil in step S4 is a mixture of a polyester smoothing agent and wormwood oil in a mass ratio of 1-2:0.5-1, and the concentration range of the polyester smoothing agent is 3.5%-5.0%.

[0037] It is worth mentioning that the high-strength, low-shrinkage polyester yarn in China in this embodiment is mainly used in the field of textiles and clothing.

[0038] It should be emphasized that the embodiments described in the present invention are illustrative rather than restrictive, and therefore the present invention is not limited to the embodiments described in the specific implementation manners. Any other implementation manners derived by those skilled in the art based on the technical solutions of the present invention also fall within the scope of protection of the present invention.

Claims

1. A method for preparing high-strength low-shrinkage polyester yarn, characterized in that: It is composed of polyester segments and high-elastic polyester yarns; The high-elastic polyester yarn comprises the following components in parts by weight: 60-80 parts of polyester masterbatch; 25-30 parts of polylactic acid fiber powder; 5-10 parts of thermoplastic polyurethane elastomer; 2-5 parts of compatibilizer; 12-18 parts of tree ash; and 2-3 parts of antioxidant. The tree ash is modified tree ash, and the preparation method of the modified tree ash is as follows: firstly boil the tree ash with 15-20% hydrogen peroxide for 18 minutes, then wash it with distilled water, dry it in an oven at 110-120°C, add 5-8 parts by weight of sodium lignin sulfonate, 2-3 parts of polyisobutylene, and 5-7 parts of talc, stir it at high speed in a water bath at 80-90°C for 2-3 hours, dry it, crush it into ultrafine powder, and then obtain the modified tree ash; The polyester chain segment comprises a terephthalic acid chain segment, an ethylene glycol chain segment and a 2,5-pyridinedicarboxylic acid chain segment, and the 2,5-pyridinedicarboxylic acid chain segments of different polyester chain segments are coordinated by Cu2+; the molar ratio of the terephthalic acid chain segment to the 2,5-pyridinedicarboxylic acid chain segment is 1:0.03-0.05; the 2,5-pyridinedicarboxylic acid chain segment has an O atom on a carbonyl group and an N atom on a pyridine involved in the coordination; the dry heat shrinkage rate of the low heat shrinkage polyester industrial yarn is 2.2±0.3% under the conditions of 177°C, 10min and 0.05cN / dtex.

2. The method for preparing high-strength low-shrinkage polyester yarn according to claim 1, characterized in that: The compatibilizer is prepared by mixing maleic anhydride grafted EVA and maleic anhydride grafted HDPE in a mass ratio of 1-2:0.5-1.

2.

3. The method for preparing high-strength low-shrinkage polyester yarn according to claim 1, characterized in that: The modified polyester is solid-phase polycondensed to increase viscosity and then wound with high-elastic polyester yarn to obtain high-strength and low-shrinkage polyester yarn; the preparation method of the modified polyester is: terephthalic acid, ethylene glycol, 2,5-pyridinedicarboxylic acid and cupric chloride are uniformly mixed and then subjected to esterification reaction and polycondensation reaction in sequence to obtain the modified polyester.

4. The method for preparing high-strength low-shrinkage polyester yarn according to claim 3, characterized in that: The preparation steps of the modified polyester are as follows: Esterification reaction: terephthalic acid, ethylene glycol, 2,5-pyridinedicarboxylic acid and cupric chloride are prepared into slurry, a catalyst and a stabilizer are added and mixed evenly, and then the esterification reaction is carried out under pressure in a nitrogen atmosphere. The pressure is normal pressure to 0.3 MPa, the temperature of the esterification reaction is 250 to 260°C, and the termination condition of the esterification reaction is: the amount of water distilled in the esterification reaction reaches more than 90% of the theoretical value; Polycondensation reaction: After the esterification reaction is completed, the polycondensation reaction in the low vacuum stage begins under negative pressure conditions. The pressure in this stage is steadily pumped from normal pressure to an absolute pressure below 500 Pa within 30 to 50 minutes. The reaction temperature is 250 to 260°C and the reaction time is 30 to 50 minutes. Then, the vacuum is continued to be pumped to carry out the polycondensation reaction in the high vacuum stage, so that the reaction pressure is further reduced to an absolute pressure below 100 Pa. The reaction temperature is 270 to 282°C and the reaction time is 50 to 90 minutes to obtain modified polyester.

5. The method for preparing high-strength low-shrinkage polyester yarn according to claim 4, characterized in that: The molar ratio of terephthalic acid, ethylene glycol and 2,5-pyridinedicarboxylic acid is 1:1.2-2.0:0.03-0.05, the amount of cupric chloride added is 20-30 mol% of 2,5-pyridinedicarboxylic acid, and the amounts of catalyst and stabilizer added are 0.01-0.05 wt% and 0.01-0.05 wt% of the amount of terephthalic acid added, respectively.

6. The method for preparing high-strength low-shrinkage polyester yarn according to claim 5, characterized in that: The catalyst is antimony trioxide, antimony glycol or antimony acetate, and the stabilizer is triphenyl phosphate, trimethyl phosphate or trimethyl phosphite.

7. The method for preparing high-strength low-shrinkage polyester yarn according to claim 6, characterized in that: The intrinsic viscosity of the modified polyester after solid phase polycondensation thickening is 1.0-1.2 dL / g.

8. Application of the method for preparing high-strength and low-shrinkage polyester yarn according to any one of claims 1 to 7, characterized in that: Used in textile and clothing fields.